Local coupling and conversion of surface waves due to Earth's rotation. Part 1: theory. Issue 1 (12th December 2020) - Snieder, Roel; Sens-Schönfelder, Christoph
SUMMARY: Earth's rotation affects wave propagation to first order in the rotation through the Coriolis force. The imprint of rotation on wave motion has been accounted for in normal mode theory. By extending the theory to propagating surface waves we account for the imprint of rotation as a function of propagation distance. We describe the change in phase velocity and polarization, and the mode conversion of surface waves by Earth's rotation by extending the formalism of Kennett for surface wave mode conversion due to lateral heterogeneity to include the Coriolis force. The wavenumber of Rayleigh waves is changed by Earth's rotation and Rayleigh waves acquire a transverse component. The wavenumber of Love waves in not affected by Earth's rotation, but Love waves acquire a small additional Rayleigh wave polarization. In contrast to different Rayleigh wave modes, different Love wave modes are not coupled by Earth's rotation. We show that the backscattering of surface waves by Earth's rotation is weak. The coupling between Rayleigh waves and Love waves is strong when the phase velocities of these modes are close. In that regime of resonant coupling, Earth's rotation causes the difference between the Rayleigh wave and Love wave phase velocities that are coupled to increase through the process of level-repulsion.